Estratégias de mitigação da ilha de calor urbana: análise de áreas verdes e superfícies aquáticas em Londrina (PR) - Coraiola, Guilherme Conor (2014)
This study, investigated the spatial and temporal distribution of air temperature and its relation to local factors such as solar radiation, rainfall and soil cover in Londrina (PR). Londrina is a medium-sized city with 515,707 inhabitants, located in the northern state of Paraná. To this end, the air temperature was monitored between May 23 and June 19, 2013 at 14 sites distributed in the south of the city, with different patterns of land cover. On average, the air temperature was higher in places dominated roofing and asphalt for days of large quantities and solar irradiance (over 12 MJ m-2). The precipitation was shown to have direct influence on the heating surface and therefore we selected a period of four days for a detailed analysis of the influence of precipitation on the air temperature. This period showed small temperature differences between the monitoring sites during the days of precipitation. From the second day, the cumulative incident solar radiation and the wide availability of soil water with the local vegetation were crucial to the large difference in air temperature between these locations and the most urbanized places, since in places with higher humidity the energy available to heat the first surface is used to evaporate the water in the soil and vegetation evaporation. The third and the fourth day showed small temperature differences between sites during the afternoon due to little moisture in the soil. However, overnight, the sites with more urban characteristics and the Lake Igapó II lost heat slower and differences in air temperature reappeared. During the case study, the differences between the air monitoring sites and the reference stations (the Igapó Lake II and Fundo do Vale) were minimal temperature under conditions of high rainfall. Places in the southwestern and northeastern zone of the study area, with predominant roof and asphalt, showed the greatest differences in temperature with respect to the reference stations, especially on the first day after rain, with the station presenting Mobille Cell temperature 4.5 °C above the temperature of the Fundo do Vale and 1.8 °C above the temperature of Lake Igapó II at 12 hours. From the second day after rainfall during the afternoons, the difference between the temperatures of the monitored locations and temperatures from the reference stations were minimal. In subsequent days, the largest temperature differences regarding the reference stations were 2.4 °C with respect to Lake Igapó II and 3.4 °C with respect to the Fundo do Valley overnight. In order to economically determine the best strategy for mitigating the urban heat island (UHI), the cost of deploying artificial lake and implementation of a grove was raised and showed that the cost to implement a forest is about 10% of the cost of implantation of an artificial lake.